A review of two-phase submerged boiling in thermal management of electronic cooling - Fan, Simiao (2022)
The increasing cooling demands of electronics have attracted more attention recently for heat removal at the component with higher heat flux and heat density. Boiling, as a two-phase cooling method, is able to achieve a rapid heat removal capacity by utilizing the latent heat from liquid to vapor phase change. It is being expected to be a good solution for cooling electronics with high heat dissipation rate. The present review examines heat transfer performance of the submerged boiling configurations, namely pool boiling, submerged jet impingement and confined jet impingement. The heat transfer characteristics examined are onset of nucleate boiling, nucleate boiling heat transfer coefficient and critical heat flux (CHF). The investigations on working fluids (traditional coolant, dielectric fluids and nanofluids) are summarized and compared. The effects of surface parameters (surface roughness, contact angle, heater size, surface orientation, surface aging and surface structures) on boiling heat transfer are discussed. Contradictory results regarding the effects of jet parameters in submerged/confined jet impingement boiling are reported, suggesting that the heat transfer mechanism of submerged/confined jet impingement boiling should be further investigated. On the other hand, it is confirmed that the submerged jet is effective in delaying CHF by providing sufficient liquid replenishing to the heated surface. A novel kind of surface structure which introduces separate liquid-vapor flow pathways in pool boiling, is discussed in detail. These surfaces introduce submerged jets in pool boiling by the elaborate surface structures but not the traditional jet generation systems. It can provide us the possibility of designing a system with heat removal capacity in submerged jet impingement level, keeping the system away from pumping power and moving parts.